1967
DOI: 10.1104/pp.42.6.831
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Basipetal Polar Transport of Auxin upon Aerobic Metabolism

Abstract: Suiiiiiwiiiry. The movement of IAA-14C through coleoptile segments of Avean and Zca has been investigated under aerobic and anaerobic conditions. The results are as follows: Zea. Using a 5-mm segment and a 2-hour transport period anlaerobic conditions reduced the total uptake of 14C from an apical donor by 74 % and the proportion of the total found in the receiving block by at least 45 %. Anaerobic conditions reduced total uptake from a basal donor by 58 % but no 14C reached the apical receiving block in eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1968
1968
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Early papers revealed that auxin transport is an active process requiring continuous respiration, supply of cellular energy in form of ATP, and physiological temperatures. [3][4][5] Here we provide in vivo pharmacological and genetic evidence that substantial portion of the polar transport of auxin in root apices is driven by vesicle-mediated secretion regulated by the PLDζ2 activity and its product PA. In the PLD2 mutant and after 1-butanol treatment, auxin fluxes measured by the IAA-sensitive microelectrode are strongly supressed despite undisturbed PINs localization.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Early papers revealed that auxin transport is an active process requiring continuous respiration, supply of cellular energy in form of ATP, and physiological temperatures. [3][4][5] Here we provide in vivo pharmacological and genetic evidence that substantial portion of the polar transport of auxin in root apices is driven by vesicle-mediated secretion regulated by the PLDζ2 activity and its product PA. In the PLD2 mutant and after 1-butanol treatment, auxin fluxes measured by the IAA-sensitive microelectrode are strongly supressed despite undisturbed PINs localization.…”
Section: Introductionmentioning
confidence: 89%
“…The secretory theory deals with the active auxin efflux whereas the chemiosmotic theory deals mainly with the passive auxin influx due to lipophilic weak acid nature of auxin and pH differences between the cytoplasm and cell wall. Ever since the polar auxin transport was shown to be dependent on active respiration and continuous ATP supply, [4][5][6] with the efflux being the decisive process, auxin efflux carriers were postulated and looked for. 8,9 Recently, manipulation of secretory activities, via phospholipase Dζ2 mutant and overexpressing lines 10 as well as its signalling product phosphatidic acid (PA), supported our earlier auxin immunolocalization data 11 that the vesicular recycling and secretion, and not just the bare presence of PINs at the plasma membrane, are essential for polar cell-cell auxin transport.…”
Section: Introductionmentioning
confidence: 99%
“…Several external factors, e.g. pH, temperature, and anoxia have been investigated (Gregory and Hancock 1956, Wilkins and Martin 1967, Goldsmith 1966, 1969, Smith and Jacobs 1968. There is also a suggestion that membrane function is responsible for polar movement.…”
Section: Introductionmentioning
confidence: 99%